Informality and Children’s School Performance in Nepal - Thapa-Parajuli, Resham; Tamrakar, Anju; Timsina, Maya (Journal of Development and Administrative Studies, 2020)
The study confirms that education is the prime determinant of whether an individual worker ends up in informal jobs that are underpaid than their formal counterparts. Educated workers are paid higher wages, mostly among wealthy quintiles with more extended work experience. Most of the females are in informal employment and are getting paid less than males. Parental work significantly relates to children's academic achievement, as the offspring of formally employed parents tend to excel. Parents' level of education shapes children's school performance through motivation, monitoring, and positive behavior. Informality might push individuals into further vulnerable situations via fewer earnings, more workload, and no access to social security. We found that the parents working in informal jobs who are already paid less than their formal counterparts are less confident about the future school performance of their kids. Thus, informality could have been a vicious circle of vulnerability that less-educated parents are underpaid and less optimistic in household human capital formation through child education. It underscores the urgency of policy interventions, including facilitating the transition from informality to formality and reducing the gender wage gap.